Тауматургия в «Повести о крещении Владимира» - Роменский, А.А. (My University, 2012)
O. Romenskyi. Thaumaturgy in the “Narration About Vladimir’s Baptism” The paper is devoted to the motive of wonderworking in the “Narration about Prince Vladimir’s Baptism” of Rus’ Primary Chronicle. Two paradigms of miracle’s perception were united in the text of the source: the pagan and the Christian one. The pagan view on wonderworking was found in the episode of “trialing the faith” by Vladimir and his envoys. The necessity of additional conviction in the power of God explains Rus’ campaign against Korsun and actions of the Prince during the siege. A loss of sight and its recovering in the font of baptism is a widespread plot in the Christian culture that symbolizes the metamorphosis of a sinner into a saint. “Korsun Legend” seems to reproduce the Byzantine concept of the christianization of Rus. The motive of the blindness healing descends from Gospel books and finds its parallels in different written traditions of the Middle Ages.
Keywords: miracle; wonderworking; healing; baptism; Chronicle; Gospel